Virtual Aspects of Studying A School Course In Astronomy (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article discusses automated and virtual experiments as new stages in the development of the experimental method of understanding natural phenomena. It is shown that, in accordance with these trends in big science, school physics experiments should also be improved. The functions of a virtual experiment in teaching are considered, and the types of models on which it can be based are determined. The problem of the methodology for including a virtual experiment in the educational process is analyzed in close connection with the question of the place and role of modern physical experience in the system of methods of scientific knowledge. The issues of using a virtual experiment as part of traditional explanatory and illustrative teaching methods are covered